A cross cultural investigation of gender: gender stereotypes of English and Xhosa undergraduate students - Robinson, Kathryn Ann (Rhodes University, Faculty of Humanities, Department of Psychology, 1990)
This study begins with the assertion that gender-role stereotypes exist in society, and that these influence the way the members of society perceive themselves and others. These stereotypes consist of sex-typed personality traits, attitudes, interests and behaviours, and they vary to a greater or lesser extent according to the culture that they originate in. Just as ordinary members of society are influenced by these stereotypes, so too are researchers, although this is not something that is often readily admitted. A great deal of research has been undertaken on gender-roles in past years, but researchers have tended to re-use existing conceptualisations of gender without examining whether they are in fact salient for the culture or generation under study. This study begins with the premise that (in South Africa as much as anywhere) before truly accurate assessment of the distributions of gender roles in a culture can be initiated, the culturally specific content of its gender-roles must be discovered. This firstly involves the description of the culture's gender-role stereotypes. Such explication would hopefully also help researchers to avoid making biased interpretations as a result of the stereotypes. Secondly, the relationship between stereotypes and self-perceptions must be established to see if scales based on the former are valid for use on the latter. This study's aim was to begin to investigate these two areas in English and Xhosa students. 94 white English speaking, and 48 black Xhosa speaking undergraduate students responded to an open ended, and a Likert-type questionnaire on various traits, attitudes and behaviours, by rating each for the "typical" male and female as well as themselves. Descriptions of stereotypes and self-ratings were obtained from performing within culture t-tests, comparing ratings of typical males and females, and male and female self ratings. Data from the open ended questionnaires was used to fill out these descriptions, which were then compared across sexes and across cultures. Gender stereotyping proved to be salient in both cultures, and gender stereotypes of the two cultures shared some similarities but also had menaingful differences. In both cultures, stereotypes and self-descriptions paralleled one another in some areas, but also differed significantly. It was concluded that the same gender-role scale would not be equally valid for use in the two cuItures, and that scales based on stereotypes would not be altogether valid for assessing self-perceptions. Various issues and implications arising from the results are discussed critically, including the proposal for a redefinition of the terms "stereotype" and "culture" to suit South African society.
Keywords: Sex role -- South Africa -- Cross-cultural studies; Stereotypes (Social psychology) -- South Africa